Pelatihan Pengelolaan Keuangan Syariah Bagi Ibu-Ibu Rumah Tangga di Kelurahan Cilangkap Cipayung Jakarta Timur - Nurhasanah, Nining (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2024)
Housewives cannot be separated from the problem of managing household money. All good and bad things can happen as a result of mismanaging family finances. The lack of priority between needs and desires is a problem that often occurs. Including how to manage productive and consumptive consumption which is the largest expenditure in the household. The aim of the service activity is to help increase understanding of how to manage finances well in accordance with sharia principles so that it can improve the economic welfare of housewives in the Cilangkap sub-district, Cipayung District, East Jakarta. The method used is a three-hour classic which includes delivering material about the differences between needs and desires, the concept of money in Islam and how to carry out sharia financial planning so as not to get caught up in financial problems that arise in the future.